Bahrain’s tertiary education reform : a step towards sustainable economic development - Magdalena Karolak (Revue des Mondes Musulmans et de la Méditerranée)
Bahrain has been experiencing along with other Gulf Council Cooperation countries a rapid development of its tertiary sector of education. The 2000's were marked by a boom in education with the opening of twelve private universities in this country of roughly 1 million inhabitants. Some institutions were locally based, while others worked in affiliation with foreign based universities. It is in sharp contrast with the 1990's, when only three public universities served as centers of higher education. The reasons behind this large-scale expansion of higher education include the growth of local and expatriate population, the planned transition from oil industry to a knowledge-based economy as well as the growing role of women in the workforce. All of these factors need to be addressed in order to assure a stable social and economic development, and education is the backbone of both. This paper examines the recent initiatives undertaken in Bahrain to monitor and ensure the quality of education of cross-border educational institutions as well as that of local education providers.